Erratum to: Hilbert series for covariants and their applications to minimal flavor violation - Benjamín Grinstein; Xiaochuan Lu; Luca Merlo; Pablo Quílez (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP06(2024)154